The relations among environmental, social disclosure, sustainable development and firm performance: Empirical evidence from mining enterprises listed on the stock market in Vietnam - La Soa Nguyen; Thi Minh Phuong Nguyen (Cogent Business & Management, 2023)
This study was conducted to examine the relationship among environmental, social disclosure, sustainable development, and firm performance. The data is collected from 71 mining companies listed on Vietnam's stock market from 2018 to 2021. Research results show that the level of environmental and social disclosure has direct impact on the level of sustainable development and firm performance of the company. Moreover, the results also show that the level of environmental and social disclosure has indirect impact on the firm performance of through the sustainability variable. Through findings, some recommendations are given for promoting social and environmental disclose of Vietnamese mining companies and similar countries to raise their awareness and responsibility for social and environmental information disclosure.
Keywords: A14; D22; G41; M48; 650; Disclosure; efficiency; environmental information; social information; sustainable development